A preliminary regional dynamic climatology of the Antarctic continent - Sabbagh, Michael E. (ERDKUNDE, 1962)
The present work attempts to give a preliminary basis for a regional dynamic climatology of Antarctica, despite the limitations existing as a result of the shortness of the observation period and the small number of observation stations. First, a basic differentiation is made between the climate of the high East Antarctic plateau and that of the coastal areas; the climate of the lower West Antarctic plateau, although showing transitional character, nevertheless belongs to a higher degree to the climate of the coastal areas. Beyond this basic dichotomy, well-defined climatic regions are identified within the area with coastal climates. The distinct regional climate characteristics are mainly a result of the perturbation element. Numerous perturbations occur in the mid-latitudes, spiraling into the interior of the continent. They are directed, mainly by anticyclonic blocking, toward favored areas, strongly affecting climatically both stretches of the coastal fringe and the lower western Antarctic plateau, while they penetrate only very rarely into the high inner eastern plateau. During the season of low solar altitude there is a greater frequency of disturbances, and it follows that at this time of year the variations of all climatic elements reach a maximum. Temperature and air pressure processes, both near the surface and in the troposphere, are characterized by large non-periodic fluctuations, the most pronounced of which extend over the widest areas and occur simultaneously through powerful layers of the atmosphere. These main fluctuations are a kind of singularities and can be associated with large-scale weather patterns. During most of the year the interior of the continent is covered by a layer of cold air. This surface skin of cold air, which is about 200 to 300 m thick and characterized by pronounced inversions and catabatic air currents, forms a discontinuity with the overlying atmosphere. Disturbances in certain weather conditions and the effects of cloud cover on radiation destroy the inversion layer extremely rarely in the distant interior, but much more frequently on the coast. The existence of a discontinuity between the surface inversion layer and the atmosphere above, and the conflict between controls aimed at isolation with perturbation elements, are the main determinants of Antarctic weather and climate. The prospects for future research on the climatology of Antarctica are now better than ever. With the continuation of the I. G. J. program and the likelihood that Antarctic observing stations will provide comparable values over a period of five or more years, new explanations for climatic characteristics of Antarctica will undoubtedly be developed, with many of the explanations developed here finding either their confirmation or refutation.